2022
DOI: 10.56098/ijvtpr.v2i2.43
|View full text |Cite
|
Sign up to set email alerts
|

Self-Selected COVID-19 “Unvaccinated” Cohort Reports Favorable Health Outcomes and Unjustified Discrimination in Global Survey

Abstract: Self-reported data collected independently by the UK-based Control Group Cooperative between September 2021 and February 2022, inclusive, from a self-selected international COVID-19 “unvaccinated” population are discussed. Data come from a cohort of 18,497 participants who provided questionnaire responses monthly. The largest numbers are from Europe, North America, and Australasia. Data were skewed towards the 40-69y age range and included 60% female respondents. Reasons for avoiding COVID-19 “vaccines” were: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Similarly, significantly increased SARS-CoV2 infection in the vaccinated population of over 18 and 50 years of age was associated with significantly increased hospitalization and deaths during the same period. The improved outcomes among the unvaccinated observed in our study are similar to the favorable health outcomes that were observed among the self-selected unvaccinated cohort 31 .…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, significantly increased SARS-CoV2 infection in the vaccinated population of over 18 and 50 years of age was associated with significantly increased hospitalization and deaths during the same period. The improved outcomes among the unvaccinated observed in our study are similar to the favorable health outcomes that were observed among the self-selected unvaccinated cohort 31 .…”
Section: Discussionsupporting
confidence: 86%
“…As a self-reported survey, the limitations included deaths that may not have been reported; nonetheless, the cohort fared better than expected. The group was perhaps unusual in that 71% partook of some combination of vitamins C, D, quercetin, zinc and off-label ivermectin or hydroxychloroquine where available [ 20 ].…”
Section: Covid-19 Modelling Versus Real-world Datamentioning
confidence: 99%
“…Tracker, 2022). Some took the shots willingly, and others to keep from being denied access to schools, restaurants, travel, or employment (Verkerk et al, 2022). At first many were anxious to submit to one of the injections, now not so many.…”
Section: Introductionmentioning
confidence: 99%